Determinants of Tax Compliance: An Investigation at The Kupang Primary Tax Service Office (KPP Pratama Kupang) - Toly, Agus Arianto; Djami, Rhesa Ekaristi Agustiano (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
Tax becomes the prime and major sources of state revenue. Taxes play an important role because it is related to state revenue. Increased income from the tax sector can be achieved by improving tax compliance from taxpayers. This study aims to explain the effect of tax administration modernization and socialization on tax compliance at the Kupang Primary Tax Office (KPP Pratama Kupang). The sample size of the study is 400 individual taxpayer samples. Data collection was done using a research questionnaire, as part of the quantitative research. The multiple linear regression analysis was used to analyse the data. The research findings indicate that the administration modernization and sanctions have negative effect on the tax compliance of registered taxpayers at the KPP Pratama Kupang.